2021
DOI: 10.46245/ijorer.v2i2.89
|View full text |Cite
|
Sign up to set email alerts
|

Development of OrSAEv Model Learning Materials Based on Role-Playing of Against Flood Disaster Mitigation Preparedness, Anxiety and Enjoyment of Junior High School

Abstract: This study aims to produce a OrSAEv model learning materials based on role-playing for effective disaster mitigation to improve flood disaster mitigation preparedness, identify anxiety and enjoyment in junior high school. This type of research is the four-Dodels. The research subjects were 29 students of grade VII at SMPN 2 Kalitidu. Based on the results of the analysis and discussion that has been carried out, it shows that the development of learning material are valid with the validity value of each Leson P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These conditions include providing sufficient time for disaster subjects. Parents also need to be invited to actively support disaster education at home by providing information and support to their children (Novia et al et al, 2021;Zunariyah et al, 2018). With these efforts, the learning environment can become more appropriate and supportive of students' understanding of disaster risks and the actions that must be taken.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions include providing sufficient time for disaster subjects. Parents also need to be invited to actively support disaster education at home by providing information and support to their children (Novia et al et al, 2021;Zunariyah et al, 2018). With these efforts, the learning environment can become more appropriate and supportive of students' understanding of disaster risks and the actions that must be taken.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the enjoyment questionnaire showed that students did not enjoy it, while the anxiety questionnaire showed that students did not feel anxious. Recommendations that can be given are the necessary pre-learning activities [29].…”
Section: Instructional Impactmentioning
confidence: 99%